The Theories of the Development of Students: A Factor to Shape Teacher Empathy From the Perspective of Motivation - Ge, Yabo; Li, Weijian; Chen, Fangyan; Kayani, Sumaira; Qin, Guihua (Frontiers in Psychology, 2021)
Empathy represents an essential prerequisite for developing effective interpersonal behavior and maintaining interpersonal relationships. Education is a result of teacher-student interaction, and, therefore, it is worth noting that teaching empathy is critical for the development of students and the professional growth of teachers. Recently, researchers began to explore the influential factors of empathy (e.g., empathic mindsets) based on motivation. Beyond their empathic attitudes, teachers also have a mindset toward the development of students. A survey study was adopted to explore the relationship between the theories of the growth of students and teacher empathy. Four hundred and eighty-four Chinese teachers completed the student development scale, the teacher empathic motivation scale, and the teacher empathy scale. The mediation model results showed that the theories of the development of students could significantly predict teacher empathy and teacher empathic motivation. The teacher empathic motivation mediated the positive relationship between the theories of the development of students and teacher empathy. This study proposes a new concept and method for teacher empathy intervention in future.